Chemical composition and antimicrobial activity of the essential oil of Ligularia persica Boiss. (Asteraceae) - Mirjalili, Mohammad Hossein; Yousefzadi, Morteza (Acta Biologica Szegediensis, 2012)
The objective of this study was to investigate chemical composition and in vitro antimicrobial activity of the essential oil of Ligularia persica growing wild in Iran. The essential oil was obtained by hydro-distillation and analyzed by GC-FID and GC/MS. Sixty-one components representing 99.0% of the total oil were characterized. The major identified components were (Z)-β-ocimene (12.5%), cis-meta-mentha-2,8-diene (8.8%), α-eudesmol (8.7%), valencene (5.9%) and 14-hydroxy-δ-cadinene (5.7%). Oxygenated sesquiterpenes (39.5%) was the main group of the plant essential oil. The essential oil exhibited moderate activity against three bacteria and a yeast, Candida albicans, with minimum inhibitory concentration (MIC) values ranging from 1.87 to 7.50 mg/ml. The best inhibitory effects were against Gram-positive bacteria, Bacillus subtilis and Staphylococcus aureus.